Malaysian-Japan Research Centre (MJARC) / Nur Irdina Sofia Kamal Jauhari - Kamal Jauhari, Nur Irdina Sofia (Faculty Of Chemical Engineering, 2022)
An essential part of the academic curriculum at Universiti Teknologi Mara (UiTM) Kampus Pasir Gudang is the industrial training module (CHE 354). In the year 2014, students were first introduced to industrial training. One of the required courses for Diploma in Chemical Engineering students is industrial training. To receive their diploma certificate, each student must participate in industrial training for 24 weeks (20 February 2022-4 August 2022) on the final semester. In addition, industrial training programmes were introduced to strengthen the necessary competencies to raise the level of graduates who can work. Students who enrol in industrial training programmes get real-world experience in the workplace that helps the market be more reliable. This is also a programme that allows students to learn, understand, and acquire knowledge about engineering problems outside of the classroom. Industrial training implies a brief services-for-experience trade between the organisation and the student. Engineers are more likely to share their knowledge in order to encourage the development of future engineers. In most cases, an intern has a supervisor who assigns specific tasks and assesses the intern's overall performance. It will be the supervisor's job to mentor and instruct an intern. The trainee must also abide by all organisational rules and regulations that have been adopted by the business.